Wprowadzanie dzieci do odbioru kultury = Children`s enculturation - Kmetko, Marzena; Kuligowska, Emilia (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
The article presents the methods of introducing children to the reception of culture. The authors have discussed pedagogical innovations: Hej, w dzień narodzenia!, Mały detektyw architektury and original authors project: W stronę Jazzu and educational project: Ferie z babcią Klawiaturą which constitute examples of extending content included in the core curriculum and concept of pre-school work. The article describes activities carried out in Miejskie Przedszkole nr 3 im. Misia Uszatka in Zielona Góra between 2015 and 2017. Results of the evaluation confirmed their purpose and meaningfulness.
Keywords: kultura w przedszkolu; program autorski; innowacja pedagogiczna; projekt edukacyjny; zajęcia muzyczne; pre-school culture; original project; pedagogical innovation; educational project; music classes